AGING AND RETIREMENT: PREPARING ADULT LEARNERS FOR POSTRETIREMENT CHALLENGES - Usman, Ya’u Haruna (Sokoto Educational Review, 2020)
Aging is process of becoming old. It is a process every living being undergo, it is complex because it brings about a complete change in all aspects of human endeavours. Aging culminates into retirement, which is disengaging from work either due to poor health or others reasons. Retirement has been found to be good for many people but devastating for most adults who did not make adequate arrangements for it. Government and private organisations should assist retirees to live happily in retirement by taking some measures such as introducing phased retirement, ensuring that the newly introduced Contributory Pension Scheme works efficiently and private organisations should also introduce educative programmes to potential retirees. In all, potential retirees should ask themselves “how am I going to live in retirement?” And “what am I going to do with my retirement years?”